2007
DOI: 10.1590/s0100-06832007000100013
|View full text |Cite
|
Sign up to set email alerts
|

Propriedades químicas de um latossolo vermelho sob plantio direto e adubação com esterco de suínos

Abstract: RESUMO(1) Trabalho parcialmente financiado pelo CNPq. Recebido para publicação em agosto de 2005 e aprovado em novembro de 2006.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
1
24

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 11 publications
6
27
1
24
Order By: Relevance
“…When 100 m 3 ha -1 of UWC was applied for two consecutive years, SOC and TN increased significantly, compared to mineral fertilization (Table 5). These results are in agreement with those of Scherer et al (2007), who evaluated the effect of annual pig slurry application on an Oxisol for three consecutive years. The authors observed an upward trend in organic matter content in the surface layer (0.0-0.10 m), which they explained by the absence of incorporation of manure and plant residues into the soil, making the mineralization of organic compounds slower and gradual in the top few centimeters of the surface layer.…”
Section: Resultssupporting
confidence: 92%
“…When 100 m 3 ha -1 of UWC was applied for two consecutive years, SOC and TN increased significantly, compared to mineral fertilization (Table 5). These results are in agreement with those of Scherer et al (2007), who evaluated the effect of annual pig slurry application on an Oxisol for three consecutive years. The authors observed an upward trend in organic matter content in the surface layer (0.0-0.10 m), which they explained by the absence of incorporation of manure and plant residues into the soil, making the mineralization of organic compounds slower and gradual in the top few centimeters of the surface layer.…”
Section: Resultssupporting
confidence: 92%
“…In addition, the ammonia nitrification process gives rise to liquid release of H + ions and reduction in soil pH when the nitrate is not absorbed in the same layer as that where the process occurs (Aita et al, 2007). In deeper layers, no significant differences in pH in water were found among the rates of pig slurry application, in agreement with studies in similar soils by Muriashi et al (2011) and Scherer et al (2007). They also found no significant changes in other properties related to soil acidity.…”
Section: Soil Chemical Propertiessupporting
confidence: 89%
“…However, no appreciable migration to deeper layers was observed, even where levels of P were high in the superficial layers, which could be due to the high soil capacity for P adsorption. Similar results were found by Scherer et al (2007), who looked at the effects of pig slurry applications in a similar Hapludox, also managed in a no-till system, and by Queiroz et al (2004), who studied the effects of pig slurry application on pastures in an Ultisol soil in the State of Rio Grande do Sul, Brazil. The P added to soil as pig slurry is adsorbed in it at specific exchange sites.…”
Section: Soil Chemical Propertiessupporting
confidence: 74%
“…Plants in the treatment T1 and T7 showed P contents below the adequate range. This was expected, since P is an element of little mobility in the soil, which is the reason for its accumulation in the superficial layer, restricting its availability to plants (Scherer, 2007). It is known that P is a nutrient required in large amounts by plants and it is responsible for storage and permutation of genetic information, with function of energy transfer as a carrier and activator of amino acids (Malavolta et al, 1997).…”
Section: Resultsmentioning
confidence: 99%